Investigation on deformation behaviors and dynamic recrystallization mechanism of spray formed Al–Zn–Mg–Cu alloy under hot compression - Zhiwu Zhang; Ruxue Liu; Dayong Li; Yinghong Peng; Guowei Zhou; Zhihong Jia; Wantai Ma (Journal of Materials Research and Technology, 2024)
The thermal deformation behavior of spray formed Al–Zn–Mg–Cu alloy was investigated by the isothermal hot compression tests at the strain rates of 0.001–10 s−1 with the temperature range of 350–450 °C. An Arrhenius constitutive equation was established by the corrected strain-stress curves, and then the processing map was constructed based on the 3D instability map and 3D power dissipation map. The influence of strain rate and temperature on both flow stress and dynamic softening has been unveiled. The results show that dynamic recovery (DRV) is the primary softening mechanism and dynamic recrystallization (DRX) is substantively retarded due to the fine dispersed particles uniformly distributed in the spray formed alloy. Continuous dynamic recrystallization (CDRX) is the primary DRX mechanism at a low temperature or high strain rate. DRX grain was observed at the grain boundaries, especially at the triple junctions. The appropriate thermal deformation condition is recommended at the temperature range from 430 °C to 450 °C and strain rates from 0.003 s−1 to 0.1 s−1.